Hop proanthocyanidins for the fining of beer - Linforth, Rob S.T.; Westwood, K.; Somani, Abhishek; Cook, David J. (Wiley, 2015)
Fining agents are used in the clarification of beers; they help to reduce the time required to sediment suspended yeast cells and ensure the clarity and colloidal stability of beer. Following an adventitious observation during dry-hopping experiments, we identified a fining activity associated with Saaz hops. Extracts of hop cones were subsequently shown to have the capacity to flocculate yeast and result in their sedimentation. This activity has since been identified in extracts of many different hop varieties and, significantly in spent hops, the co-product resulting from commercial extraction of hops with either CO2 or ethanol. Here we illustrate the activity of the novel finings extracted from spent hops following CO2 extraction of Galena hops. The sediments formed on fining were compact, relative to those obtained when commercial isinglass was used to fine the same beers. The hop extracts were also effective in reducing 90° haze in beers under conditions designed to mimic both cask ale (12 °C) and lager (4 °C) type applications. The compounds responsible for the fining activity appear to be large (30–100 kDa, or more) polyphenols. Analysis of the polyphenols using colourimetric tests indicated the presence of proanthocyanidins. On acidic hydrolysis these generated cyanidin, which would be derived from a polymer composed of catechin and epicatechin subunits. The presence of these materials in spent hops offers the possibility to develop commercial products, with desirable fining properties, from an existing co-product stream. Furthermore, the finings are derived from a traditional ingredient of the brewing process.